Vietnam - Quỹ Châu Á; Quỹ Châu Á
The article aims to introduce The Asia Foundation in Vietnam, whose programs are built around four key themes: 1. Advancing effective governance; 2. Supporting economic policy dialogue and private sector development; 3. Addressing environment and climate change challenges; 4. Empowering women and vulnerable populations.